2020
DOI: 10.3390/jcm9124057
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 and Viral Sepsis: Immune Dysfunction and Implications in Kidney Failure

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causal agent of coronavirus disease 2019 (COVID-19), first emerged in Wuhan, China. The clinical manifestations of patients infected with COVID-19 include fever, cough, and dyspnea, up to acute respiratory distress syndrome (ARDS) and acute cardiac injury. Thus, a lot of severe patients had to be admitted to intensive care units (ICU). The pathogenic mechanisms of SARS-CoV-2 infection are mediated by the binding of SARS-CoV-2 spikes to the human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 171 publications
(229 reference statements)
0
18
0
2
Order By: Relevance
“…This study further noted that 35.5% patients developed AKI, and 12.3% of them succumbed to death [ 55 ]. Still, the incidence of AKI in SARS-CoV-2infection is lower than in SARS and MERS [ 56 ]. ACE-2 is the main binding site for SARS-CoV-2, and it is expressed in lung tissue and other vital organs, including the kidneys.…”
Section: Introductionmentioning
confidence: 99%
“…This study further noted that 35.5% patients developed AKI, and 12.3% of them succumbed to death [ 55 ]. Still, the incidence of AKI in SARS-CoV-2infection is lower than in SARS and MERS [ 56 ]. ACE-2 is the main binding site for SARS-CoV-2, and it is expressed in lung tissue and other vital organs, including the kidneys.…”
Section: Introductionmentioning
confidence: 99%
“…Strong cytokine storms are widely present in patients with severe COVID-19. The elimination of cytokine storms can improve clinical results, including acute respiratory distress syndrome, acute heart injury and acute renal failure [ 40 , 41 ]. These results indicated that the autophagy interaction network established based on the ceRNA and protein interaction mechanisms may play an important role in the cytokine storm.…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 is the receptor for SARS-CoV-2 [29][30][31], which is responsible for the COVID-19 outbreak, giving rise to the following two questions: will renal injury be increased in COVID-19 patients with diabetes and will ACEi/ARB treatment have an impact on the renal outcome of COVID-19 patients with diabetes? COVID-19 patients with T2DM have higher acute kidney injury prevalence rates than individuals without diabetes [32], which may be explained by ACE2-mediated viral cytopathic effects [26,33]. Some studies [34,35] implied that RAAS inhibitors increased the risk of acute kidney injury, suggesting more concern about renal outcomes in patients with severe COVID-19 with diabetes who are treated with…”
Section: Discussionmentioning
confidence: 99%